Transcriptomic Analysis Reveals the Role of tmRNA on Biofilm Formation in Bacillus subtilis - Shanshan Xu; Qianqian Cao; Zengzhi Liu; Junpeng Chen; Peiguang Yan; Bingyu Li; Ying Xu (Microorganisms, 2022)
Bacillus strains are widely distributed in terrestrial and marine environments, and some of them are used as biocontrol organisms for their biofilm-formation ability. In Bacillus subtilis, biofilm formation is fine-tuned by a complex network, a clear understanding of which still requires study. In bacteria, tmRNA, encoded by the ssrA gene, catalyzes trans-translation that can rescue ribosomes stalled on mRNA transcripts lacking a functional stop codon. tmRNA also affects physiological bioprocesses in some bacteria. In this study, we constructed a ssrA mutant in B. subtilis and found that the biofilm formation in the ssrA mutant was largely impaired. Moreover, we isolated a biofilm-formation suppressor of ssrA, in which the biofilm formation was restored to a level even stronger than that in the wild type. We further performed RNAseq assays with the wild type, ssrA mutant, and suppressor of ssrA for comparisons of their transcriptomes. By analyzing the transcriptomic data, we predicted the possible functions of some differentially expressed genes (DEGs) in the tmRNA regulation of biofilm formation in B. subtilis. Finally, we found that the overexpression of two DEGs, acoA and yhjR, could restore the biofilm formation in the ssrA mutant, indicating that AcoA and YhjR were immediate regulators involved in the tmRNA regulatory web controlling biofilm formation in B. subtilis. Our data can improve the knowledge about the molecular network involved in Bacillus biofilm formation and provide new targets for manipulation of Bacillus biofilms for future investigation.